Danza integrada e inclusión escolar en los niños de preparatoria de la Escuela de Educación Básica Municipal Héroes del Cenepa en la Ciudad de Loja, periodo 2022-2023 - Suarez Ordoñez, Samantha Elizabeth (2023)
School inclusion helps children develop inclusive attitudes and values to demonstrate actions framed in respect, tolerance, kindness, and support toward all their classmates and teachers. The elements mentioned above are necessary to preserve a harmonious atmosphere in the classroom where children are surrounded by an environment aimed at equal opportunities regardless of their social class, culture, religion, customs, and skin color. Such aspects are considered irrelevant when seeking to achieve true school inclusion. For this reason, this research study sought to determine how integrated dancing fosters school inclusion in preschool children at Héroes del Cenepa Municipal Middle School in the city of Loja, period 2022-2023. This research was quantitative, with a descriptive scope and a pre-experimental design, using deductive and analytical-synthetic methods. The observation guide based on the inclusion index developed by Booth and Aiscow served as a pre and post-test. The initial results showed that 90% of the children did not display inclusive practices, but after the application of the activity guide called "Dancing in diversity, we form a unit", there was a noteworthy improvement of 86% both in culture and in inclusive practices. Therefore, the results demonstrated the effectiveness of integrated dancing as a method that favors inclusion, promoting positive attitudes in children regarding diversity and establishing a more harmonious environment. Keywords: integrated dancing, diversity, school inclusion, dance stypes